-
With the double angle formula:
y=cosx-2(cosx)^2+1
Then use the properties of the quadratic function.
Let t=cosx, then -1<=t<=1
That is, find the minimum value of y=-2t 2+t+1.
The axis of symmetry of this quadratic function is t=1 4
So it increases monotonically on [-1,1 4] and decreases monotonically on [1 4,1], so just try t=-1 and t=1 to see which is smaller. When substituting finds t=-1, y=-2 is the smallest.
So the minimum value of y is -2
-
y=cosx-cos2x=cosx-(2cosx^2-1)=1+cosx-2cosx^2
cosx=1 4. The function is maximum, y=1+1 4-1 8=9 8
When coxx=-1, the minimum function is y=1-1-2=-2
-
y=cosx-cos2x=cosx-(2cosx^2-1)=1+cosx-2cos^2
The image of this function is symmetrical with respect to x=1 4, where x is minus one and ymin is minus two.
-
y=cosx-2cos²x+1
cosx belongs to [-1,1].
When cosx=-1, y obtains a minimum value of -2
-
Because it is square + square + absolute value = 0
squared, the absolute value must be greater than or equal to 0
So here it is only possible:
a-2b-4=0
2b+c=0
a-4b+c=0
Three unknowns, three equations, and you can solve it.
a-2b-4=2b+c=0
So a-4b-4-c=0=a-4b+c
c=-2 is substituted into 2b+c=0
Get b = 1 and substitute a-2b-4 = 0
Get a=6 because a=6, b=1, c=-2
So substituting 3a+b-c gets 21
-
Because (a-2b-4) +2b+c) =-|a-4b+c|, so (a-2b-4) +2b+c) =0, a-4b+c=0
This gives a-2b-4=0
2b+c=0
a-4b+c=0
Finally, we find a=6 b=1 c=-2
-
(a-2b-4)²+2b+c)²+a-4b+c|=0 to obtain: a-2b-4=0;2b+c=0;a-4b+c=0 is obtained by the third formula: a-2b-4b+2b+c=0 Substituting the first and second formulas into the first formula yields b=1, c=-2, a=6
then 3a+b-c=21
-
(a-2b-4)²+2b+c)²+a-4b+c|=0 because: if the sum of several polynomials is zero, then each term of this polynomial is zero, so: a-2b-4=0 , 2b+c=0 , a-4b+c=0 , expressed by the algebraic expression of b, and then substituted into obtain:
a=6,b=1,c=-2
Substituting a=6, b=1, c=-2 into 3a+b-c yields: 3 6+1-(-2)=21
-
The root of the equation a = root number 3, b = 2 - root number 3
c=2, because a+b=c, the triangle does not exist.
-
The first equation has no solution to the problem.
-
Solution: x -2x + 3 (2-3) = 0
x1=√3 ; x2=2-√3
a=√3,b=2-√3
x²-4=0
x1=2 ;x2=-2
c=2 and a+b=c
Triangles with a, b, and c as sides do not exist.
1) The function image opening is downward, there are m2-2 0 >>>More
1 part of blue flower, 2 parts of yellow flower, 3 parts of safflower, blue flower accounts for 1 6 of the total area, yellow flower accounts for 1 3, and safflower accounts for 1 2 >>>More
You can assume that you bring one yuan, then 1 15 yuan is the ** of the language book, and 1 24 yuan is the ** of the math book. >>>More
Mr. Ma wants to use iron wire to make a cuboid with a length of 4cm, a height of 5cm, a width of 3cm and a cube with an edge length of 8cm. >>>More
Because x 2 + y 2 > = 2xy
y^2+z^2>=2yz >>>More